2020
DOI: 10.1111/jsr.13118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute sleep deprivation on H reflex and V wave

Abstract: The impact of sleep deprivation on muscular strength and power remains poorly understood. We aimed to determine the acute effects of 24 hr of sleep deprivation on H-reflex and V-wave excitability. Fourteen healthy young adults (eight men, six women) were included. Participants visited the laboratory on two different occasions, without and with 24 hr of sleep deprivation. In each session, participants were tested for maximal voluntary contraction (MVC) of the plantar flexors and dorsiflexors, soleus H-and M-rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 45 publications
3
12
0
Order By: Relevance
“…Some studies included in this meta-analysis assessed the influence of sleep loss on more than one performance task, either belonging to the same category [40,41,53,58,59,63,64,[75][76][77][78][79][80][81][82][83][84], or different categories [41, 43, 44, 56-59, 61, 62, 64, 65, 75, 77-81, 85-102]. For example, Souissi et al [78] measured anaerobic power in two separate tasks (i.e., squat jump and Wingate test).…”
Section: Exercise Task Classificationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies included in this meta-analysis assessed the influence of sleep loss on more than one performance task, either belonging to the same category [40,41,53,58,59,63,64,[75][76][77][78][79][80][81][82][83][84], or different categories [41, 43, 44, 56-59, 61, 62, 64, 65, 75, 77-81, 85-102]. For example, Souissi et al [78] measured anaerobic power in two separate tasks (i.e., squat jump and Wingate test).…”
Section: Exercise Task Classificationsmentioning
confidence: 99%
“…However, serial measures were accepted if the preceding test was deemed unlikely to have influenced performance on the subsequent test. For example, if the preceding test used different muscle groups (e.g., knee extensor maximum voluntary contraction (MVC) and knee flexion MVC) [53,76,82,83] or a contralateral muscle group [82], or if the same test was repeated at separate times of the day (e.g., once at 0600 h, then at 1700 h) [43,53,62,64,[79][80][81]90], then each measurement was included and considered as a separate 'outcome measure'.…”
Section: Exercise Task Classificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is worth considering the effects of sleep deprivation on the muscle coordination (e.g., agonist/antagonist muscle activity), which could subtly or substantially impact movement control tasks such as postural balance. Gonçalves et al (2021) showed that the antagonist/agonist level of co-contraction or co-activation increased during maximal voluntary contraction following sleep deprivation. This change of the antagonist/agonist co-activation would mean that the muscle coordination was affected after sleep deprivation.…”
Section: Neuromuscular Functionmentioning
confidence: 99%